Engelmann spruce and subalpine fir stand dynamics in north central Colorado - Derderian, Drew Phillip, author; Binkley, Daniel, advisor; Paschke, Mark, committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2015)
Stemwood biomass and production were measured in a 600-year chronosequence of stands consisting of Engelmann spruce and subalpine fir in the Colorado Front Range. The stands were part of a chronosequence established and measured in 1984. The original chronosequence showed near-constant biomass of spruce after approximately 250 years of development. Spruce production also had remained nearly constant after an initial rise and fall during the first 250 years. Fir biomass decreased more than that of spruce after around 150 years. Fir biomass remained at lower consistent sub-dominate values through the end of the chronosequence. Fir's high production from early stand development decreased and remained constant after approximately 175 years of development. Changes over the most recent 29 years did not follow the patterns in the 1984 chronosequence: spruce biomass dropped by 70% with little change in fir biomass. This resulted in a 47% average decrease in total stand biomass since 1984. Stand biomass showed no relationship with stand age. Spruce beetle-kill appeared to have played a major role in live biomass decline in all stands. Net increment was negative in fir as increases in fir production were more than offset by fir mortality. The stands investigated have developed from post-fire initiation and, although there was no evidence of subsequent major disturbance in 1984, severe beetle infestation since then has altered expected trends in spruce-fir forest structure. Stand age pattern projections will likely continue to be altered by disturbances and changing disturbance regimes.